ln(3+x)+ln(6-x)=ln(15)

Simple and best practice solution for ln(3+x)+ln(6-x)=ln(15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(3+x)+ln(6-x)=ln(15) equation:


Simplifying
ln(3 + x) + ln(6 + -1x) = ln(15)
(3 * ln + x * ln) + ln(6 + -1x) = ln(15)
(3ln + lnx) + ln(6 + -1x) = ln(15)
3ln + lnx + (6 * ln + -1x * ln) = ln(15)
3ln + lnx + (6ln + -1lnx) = ln(15)

Reorder the terms:
3ln + 6ln + lnx + -1lnx = ln(15)

Combine like terms: 3ln + 6ln = 9ln
9ln + lnx + -1lnx = ln(15)

Combine like terms: lnx + -1lnx = 0
9ln + 0 = ln(15)
9ln = ln(15)

Reorder the terms for easier multiplication:
9ln = 15ln

Solving
9ln = 15ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-15ln' to each side of the equation.
9ln + -15ln = 15ln + -15ln

Combine like terms: 9ln + -15ln = -6ln
-6ln = 15ln + -15ln

Combine like terms: 15ln + -15ln = 0
-6ln = 0

Divide each side by '-6'.
ln = 0

Simplifying
ln = 0

The solution to this equation could not be determined.

See similar equations:

| 2x+35=12x-5 | | 2kx+9=4x+kx | | -(9-c)= | | 3/5=2000 | | x+0.05x=168 | | c=28/3x15 | | x^2+4x+4-9=0 | | c=28/3m | | x+3x+x-12=180 | | x+3x+x-15=180 | | x+3x+(x-12)=180 | | 3e+1=10p | | 5.4/.12 | | 54./.12 | | .7x-.3=.6x+4 | | tgx=0.0042 | | -4*96/100 | | 9(7x-1)=7(7x+1)+390 | | 4sin(x/2)cos(x/2) | | 11*(-11)= | | 25a^4-10a^2b^2+b^4=0 | | 3x+22-2x=9+4x-5 | | 63-7=36x+560 | | (x^2-3x+1)(x^2+3x-3)=5 | | 8x^2+117x-45=0 | | 272000/600 | | y^1=8y^2+91 | | 13-w=1-4w | | 4x^8-4ax^4+a^2=0 | | y^1=4y^2+556 | | 2x+16x^4=0 | | 4.9t^2-12t-65=0 |

Equations solver categories